Thermodynamics for engineers - Potter, Merle C. (Schaum's outline, 2014)
Concepts, definitions and basic principles - Properties of pure substances - Work and heat - The first law of thermodynamics - The second law of thermodynamics - Entropy - Reversible work, irreversibility and availability - Gas power cycles - Vapor power cycles - Refrigeration cycles - Thermodynamic relations - Mixtures and solutions - Combustion - Sample exams for a semester course for engineering students - Appendices.